2021
DOI: 10.21203/rs.3.rs-790299/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 myth-busting: an experimental study

Abstract: BackgroundCOVID-19 misinformation is a danger to public health. A range of formats are used by health campaigns to correct beliefs but data on their effectiveness is limited. We aimed to identify A) whether three commonly used myth-busting formats are effective for COVID-19 myths, immediately and after a delay, and B) which is the most effective.MethodsWe tested whether three common correction formats could reduce beliefs in COVID-19 myths: (i) question-answer, ii) fact-only, (ii) fact-myth. n = 2215 participa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…Furthermore, not only are our percentage changes very similar to Altay's chatbot condition effects, who were recruited from the general population and not specifically against vaccination, but also much greater than those in previous studies, for example when influenced by norms, participants only showed a 5% decline in rating themselves as 'undecided' or 'against' vaccination (Moehring et al, 2021), whereas we found a 16% decline. Previous research also suggests that using Q&A style information is more effective than presenting pure fact-based information, again reporting similar effects to ours (Challenger et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, not only are our percentage changes very similar to Altay's chatbot condition effects, who were recruited from the general population and not specifically against vaccination, but also much greater than those in previous studies, for example when influenced by norms, participants only showed a 5% decline in rating themselves as 'undecided' or 'against' vaccination (Moehring et al, 2021), whereas we found a 16% decline. Previous research also suggests that using Q&A style information is more effective than presenting pure fact-based information, again reporting similar effects to ours (Challenger et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…Brand, Department of Psychology, University of Sheffield, Sheffield, S1 1HD. E-mail: c.brand@sheffield.ac.uk al., 2021), presenting information on the timeline of vaccine development (Thorpe et al, 2021), different styles of mythbusting (Challenger, Sumner, & Bott, 2021), the use of social norms (Moehring et al, 2021), framing messaging in terms of individual risk preferences (Trueblood, Sussman, & O'Leary, 2020) and even chatbots (Altay, Hacquin, Chevallier, & Mercier, 2021), all with varying levels of success.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, not only are our percentage changes very similar to Altay et al's chatbot condition effects, who were recruited from the general population and not specifically against vaccination, but also much greater than those in previous studies, for example when influenced by norms, participants only showed a 5% decline in rating themselves as 'undecided' or 'against' vaccination [4], whereas we found a 16% decline. Previous research also suggests that using question and answer (Q&A) style information is more effective than presenting pure fact-based information, again reporting similar effects to ours [3].…”
Section: Discussionsupporting
confidence: 84%
“…Appropriately, huge amounts of attention and research effort have been directed towards how to increase COVID-19 vaccination uptake. Owing to the urgency and impact of the problem, a multi-pronged attack is warranted, and thus research rightly spans many different strategies, from pre-empting misinformation on social media [ 1 ], presenting information on the comparison of COVID-19 symptoms to vaccination side-effects [ 2 ], presenting information on the timeline of vaccine development [ 2 ], different styles of myth-busting [ 3 ], the use of social norms [ 4 ], framing messaging in terms of individual risk preferences [ 5 ], and even chatbots [ 6 ], all with varying levels of success.…”
Section: Introductionmentioning
confidence: 99%